Perilaku Ibu Memanfaatkan Pelayanan Kesehatan Selama Hamil dan Penggunaan Kontrasepsi Selama Menyusui - Indarwati Siswanto Agus Wilopo, Djauhar Ismail (Berita Kedokteran Masyarakat (BKM), 2007)
Background: The 2002-2003 Indonesian Demographic and Health Survey (IDHS) data indicated an increase up to 41% in the number of children not breastfed until two years old. Previously, according to 1997 IDHS data, there were only 34% babies who were weaning before they had reached two years. This increase was in line with the increasing number of pregnant mothers utilizing health care and hormonal contraceptives.Objective: to explore the correlation between the length of breastfeeding and the behaviors of Indonesian pregnant mothers utilizing health care and hormonal contraceptives.Methodology: Using the cohort retrospective approach, the research was conducted upon 5940 mothers, who were 15 years to 49 years old. Each had at least one under-five-years-old child.  The proportional Odds Model was employed to analyze the ordinal out come of the study. The life table served to show the continuity of breastfeeding. The variables taken were the length of breastfeeding. ANC visits, contraceptive usage, ownership assets, educational level, working status, parity, residence, prelactal liquid and milk from bottles.Findings; The probability of breastfeeding up two years old between mothers with ANC visits and without ANC visits were notdifferent. The probability of breastfeeding until two years old between mothers using non-hormonal contraception was higher compared to hormonal ones. The risk of weaning before two years in mothers using hormonal contraception was higher (1.5 times) compared to those using non-hormonal contraception.Conclusion: Factors significantly correlated with breastfeeding period were women's behaviors and characteristic as well as the family's economic status, the declining median of breastfeeding period of Indonesian mothers had strong correlation with hormonal contraceptive usage and bottles milk.Keywords: breastfeeding, antenatal care, contraceptives, demography